ANALISA PENGARUH PERTUMBUHAN PENJUALAN DAN AKTIVA LANCAR TERHADAP HARGA SAHAM PADA PERUSAHAAN INDUSTRI BARANG KONSUMSI DI BURSA EFEK INDONESIA (BEI) Ã¢â‚¬Â - Meti Zuliyana (JURNAL KOMPETITIF, 2014)
The capital market is an appropriate representation for assessing the condition of the company - a company in a country because almost all industries are represented in it and one of the effective means to accelerate the development of a country and the development of capital markets provide a source of investment for investors. One activity is to invest in companies issuing shares. To invest in shares of analysis needed to measure the value of shares, namely fundamental analysis and technical analysis. The purpose of this study was to determine Influence Sales Growth ( Sales Growth ) And Assets On Stock Price On Consumer Goods Industry Company In Indonesia Stock Exchange (IDX). This study used secondary data obtained from the annual financial statements published by the Indonesia Stock Exchange (IDX) using a sample of 12 consumer goods industry during the period 2006-2009. For analysis and hypothesis testing used multiple regression analysis model by using SPSS version 16.0. From the results of the study by using a multiple linear regression showed that in partial sales growth (Sales Growth) t value of -0.122 <t table value of 1.679 with a significance level of more than 0.05 is 0.904. While the variable current assets (Current Assets) t value of -0.222 <t table value of 1.679 with a significance level of more than 0.05 is 0.825, the variable sales growth (Sales Growth) and current assets have no significant effect terhada stock prices, whereas in simultaneously throughout the company's fundamentals: sales growth (Sales Growth) and current assets have a significant effect on stock prices with a level of significance (0.05). Instead, in this study can cover all companies listed on the Indonesia Stock Exchange and more attention to factors - external factors (inflation, exchange rate movements of currencies, interest rates, political conditions) and expectations (regional economic conditions) that more has influence on stock prices. Keywords: Stock price, Sales Growth (Sales Growth), Current Assets.